Republic of Belarus : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Belarus's economy has performed well owing to its strong macroeconomic policies, which facilitated rapid real income growth, near-full employment, and a reduction in poverty to the lowest level in the Commonwealth of Independent States (CIS). Executive Directors welcomed the disciplined monetary and fiscal policies. They commended the efforts to curb budgetary transfers and subsidies, reduce the tax burden, and strengthen the financial system. They appreciated the National Bank of the Republic of Belarus (NBRB) in strengthening the supervisory frameworks, and stressed the need for fiscal tightening and strengthening of its policies, reforms, and economic performance.